Problem-Based Learning with Scaffolding: Enhancing Chemical Conceptual Understanding, Curiosity, Communication Skills, and Character - Yusnidar Yusnidar; Dwi Agus Kurniawan; Miftahul Zannah Azzahra (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This research aims to determine the comparison and influence of problem-based learning integrated with scaffolding on students' conceptual understanding, curiosity and communicative character. Methodology: The type of research used in this research is quantitative with an experimental type with a posttest only control group design. The population in this study were all chemistry education students for the 2021/2022 academic year consisting of 4 classes. The sampling technique used was cluster random sampling so that the samples were class A, class B and class C, each consisting of 21 students. The data collection instrument used was a test instrument to determine students' understanding of concepts after carrying out the learning process using the method used, a curiosity character questionnaire and a communicative character questionnaire. Main Findings: The results of this research are that there are differences and influences of the application of the integrated scaffolding problem-based learning model on students' conceptual understanding, curious character and communicative character. Novelty/Originality of this study: Through this exploration, research reveals that the comparison between the use of Problem Based Learning and Scaffolding methods in the context of understanding chemical concepts not only strengthens academic competence, but also forms the character of students who are passionate about knowledge and communicate effectively.